2022
DOI: 10.3390/toxics10110706
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Dose-Range Chemical Toxicity using Novel Hybrid Deep Machine-Learning Method

Abstract: Humans are exposed to thousands of chemicals, including environmental chemicals. Unfortunately, little is known about their potential toxicity, as determining the toxicity remains challenging due to the substantial resources required to assess a chemical in vivo. Here, we present a novel hybrid neural network (HNN) deep learning method, called HNN-Tox, to predict chemical toxicity at different doses. To develop a hybrid HNN-Tox method, we combined two neural network frameworks, the Convolutional Neural Network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…A vector was created for the SMILES of each compound by converting each character in the SMILES string to its corresponding index in the dictionary. The resulting vector for the SMILES was padded with zeros or truncated so that it was of uniform length, L. We previously described in detail the SMILES preprocessing of chemicals [ 76 , 77 , 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…A vector was created for the SMILES of each compound by converting each character in the SMILES string to its corresponding index in the dictionary. The resulting vector for the SMILES was padded with zeros or truncated so that it was of uniform length, L. We previously described in detail the SMILES preprocessing of chemicals [ 76 , 77 , 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…CNNs have been found to be successful for use in toxicity prediction tasks in the literature and are very popular QML analogues of classical architectures. The popularity of QCNNs partly stems from only needing to operate on small sections of input data at a time, rendering them feasible for NISQ devices. We employ a quantum-classical architecture where the first convolutional layer is replaced by a quantum circuit and is subsequently followed by classical pooling, a classical convolutional layer, and a fully connected layer, as depicted in Figure .…”
Section: Architecture and Data Setmentioning
confidence: 99%
“…The high attrition rate of small-molecule drug candidates is primarily attributed to safety and toxicology in the preclinical or clinical phase . Numerous in vitro and in vivo experiments are required to assess drug toxicity, which are time-consuming and expensive, and in vivo animal tests may arouse ethical concerns . Furthermore, the differences in physiology and genetics between humans and animal models can cause the inapplicability of toxicity prediction to humans. , Studies have shown that the absence of toxicity observations from preclinical animal tests does not imply harmlessness for humans. , Therefore, it is crucial to utilize computational toxicology to assist in high-throughput drug toxicity prediction.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Numerous in vitro and in vivo experiments are required to assess drug toxicity, which are time-consuming and expensive, and in vivo animal tests may arouse ethical concerns. 6 Furthermore, the differences in physiology and genetics between humans and animal models can cause the inapplicability of toxicity prediction to humans. 7 , 8 Studies have shown that the absence of toxicity observations from preclinical animal tests does not imply harmlessness for humans.…”
Section: Introductionmentioning
confidence: 99%